Strategi Pengembangan Sumber Daya Manusia Aparatur pada Pemerintah Daerah Kabupaten Biak Numfor - Hermanu Iriawan (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
Apparatus resource development has a very important role in the organization. This study aims to determine the apparatus resource development strategy in the local government of Biak Numfor Regency. The research method used is a qualitative approach. Data collection was carried out through Focus Group Discussions (FGD, observation and interviews, researchers also conducted document analysis and review of documentation. The results showed that the apparatus human resource development strategy in the Regional Government of Biak Numfor Regency was prepared carefully and was based on scientific methods and guided by the on the skills needed by the organization, as for the human resource development strategy of the apparatus of the Biak Numfor district government, namely, job rotation, education and training. Development aims to improve the technical, theoretical, conceptual and moral capabilities of human resources so that their work performance is good and achieves results.